BS EN ISO 28199-2. Paints and varnishes. Evaluation of properties of coating systems related to the application process. Part 2. Colour stability, process hiding power, re-dissolving, overspray absorption, wetting, surface texture and mottling (23rd June 2020) - British Standards Institution,
No abstract available